A model of self-oscillation processes of a physical linear viscoelastic rod - M.M. Mansurov (Genius Journals, 2023)
This article considers the problem of modeling self-oscillating processes of a physical linear viscoelastic rod in a gas flow, taking into account linear dependencies.
Keywords: viscoelasticity; rod; self-oscillations; physical linearity